2010
DOI: 10.1080/03630242.2010.530928
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Delays to Diagnosis and Treatment of Breast Cancer in Women in a Louisiana Urban Safety Net Hospital

Abstract: Only lung cancer surpasses breast cancer as a cause of death from cancer. However, the burden of cancer is not borne equally across racial and ethnic groups. In the United States, African American women have significantly higher mortality rates from breast cancer than white women. Delayed follow-up of breast abnormalities and delays from diagnosis to treatment may contribute to higher mortality. This study examined factors associated with delays to diagnosis and treatment of breast cancer in a group of white a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 15 publications
4
33
0
6
Order By: Relevance
“…Neste estudo, as características que influenciaram no desfecho para o conjunto do país foram: ano do diagnóstico, estadiamento da doença, origem do encaminhamento, raça/cor da pele, escolaridade e estado conjugal, corroborando, em sua maioria, estudos anteriores 11,17,27,28,29,30 . Porém, na análise múltipla estratificada por macrorregiões do Brasil, os resultados obtidos demonstram diversidade de fatores que interferem no intervalo de tempo entre o diagnóstico e o início do tratamento do câncer de mama.…”
Section: Resultsunclassified
“…Neste estudo, as características que influenciaram no desfecho para o conjunto do país foram: ano do diagnóstico, estadiamento da doença, origem do encaminhamento, raça/cor da pele, escolaridade e estado conjugal, corroborando, em sua maioria, estudos anteriores 11,17,27,28,29,30 . Porém, na análise múltipla estratificada por macrorregiões do Brasil, os resultados obtidos demonstram diversidade de fatores que interferem no intervalo de tempo entre o diagnóstico e o início do tratamento do câncer de mama.…”
Section: Resultsunclassified
“…8,[33][34][35] Inability to differentiate the type and sequence of therapy, particularly neoadjuvant, radiation and surgical treatment sequence, was a limitation for many of the previous investigations. Although time is required for preoperative evaluation before the appropriate surgery is performed, it is shown that ‡ 2 months delay in initiating surgical treatment can negatively impact survival.…”
Section: Discussionmentioning
confidence: 99%
“…Zaobserwowano jednak pewną poprawę w zakresie obniżenia stopnia zaawansowania nowotworu w momencie rozpoznania [1], chociaż rozpoczęcie leczenia przez chore na raka piersi w Polsce nadal jest opóźnione. Opóźnienie w podjęciu leczenia nie jest wyłącznie polskim doświad-czeniem [3,[5][6][7][8][9][10][11][12][13]. Wśród przyczyn opóźnienia wymieniane są przyczyny zależne od chorych, od lekarzy oraz systemu opieki zdrowotnej [14].…”
Section: Wstępunclassified
“…w czerniaku, jest lepsze, jeżeli rozpoznanie zostanie postawione w czasie krótszym niż 3 miesiące od pierwszych objawów klinicznych [5,15]. Na opóźnienie procesu diagnostyczno-terapeutycznego ze strony chorych wpływa szereg czynników, w tym wiek, stan społeczno-ekonomiczny, wykształcenie, czynniki etniczne, kulturowe i psychologiczne [3,5,[6][7][8][9][16][17][18]. Wszystkie te elementy warunkują w mniejszym lub większym stopniu zachowania zdrowotne i mogą wpływać na zmniejszenie lub zwiększenie opóźnienia.…”
Section: Wstępunclassified